THE IMPACT OF MARKETING TOOLS ON THE EFFECTIVENESS OF STRATEGIC MANAGEMENT OF AGRICULTURAL ENTERPRISES - PYVOVAROV, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the study of marketing tools’ impact on the effectiveness of strategic management in agricultural enterprises. It is determined that the effective use of marketing tools provides a deeper understanding of market conditions, helps identify consumer needs, analyzes competitors, and adapts strategies to a changing environment. This allows agricultural enterprises to optimize their activities and achieve long-term goals. It is proven that marketing tools contribute to adaptation to external challenges. Thanks to data analysis, demand forecasting, and sales planning, enterprises can respond more effectively to these challenges. It is established that digitalization is the driving force of marketing transformations. Digital marketing tools open up new opportunities for building relationships with customers, expanding sales markets, and reducing costs. Implementing these tools significantly increases the effectiveness of strategic management. It is substantiated that marketing increases the competitiveness of agricultural enterprises. The systematic use of marketing strategies allows agricultural enterprises to create unique sales offers, develop brands, optimize the product range, and improve communication with the target audience. This contributes to the formation of long-term competitive advantages. The study of the impact of marketing tools on strategic management is of practical importance, as it allows agricultural enterprises to use resources more efficiently, increase financial performance, and remain competitive in local and global markets. Thus, marketing tools contribute to the effective strategic management of agricultural enterprises and act as a critical factor in their long-term success and stability in a dynamic market.